Aphrodisiac potential of the aqueous extract of melicope pteleifolia (Champ ex benth) t. g. hartley in sprague dawley rats - Mohd Najib, Nazizarini (2019)
Infertility is the inability of a sexually active spouse that does not possess any contraceptives to achieve pregnancy within a year. Reduced sperm quality and sperm count are among contributing factors that can cause infertility in male. This study aims to investigate the beneficial effects of Melicope pteleifolia aqueous extract (MPAE) consumption on aphrodisiac effect in adult male Sprague-Dawley rats. A total of 30 male Sprague Dawley rats were divided equally into five different groups. MPAE was given by orally gavage for 28 days at a dose of 100mg/kg, 200 mg/kg and 500 mg/kg body weight to the animals of group II (n=6), III (n=6) and IV (n=6), respectively. The animals of group I (negative control, n=6) had distilled water and group (positive control, n=6) had sildenafil citrate. Results were analysed using one-way ANOVA test and the data were significant at p<0.05. Acute toxicity study, male sexual behaviours, penile erection index, sperm parameters, testosterone level, anabolic effects and histology of testes were evaluated. The result shows no mortality and signs of toxicity recorded in behaviour changes, abnormalities in clinical appearances and body weight changes for a duration of 28 days. It is concluded the Lethal Dose at 50 percent is more than 5000 mg/kg of MPAE. In this present study, rats treated with MPAE appeared to be more sexually active in male sexual behaviours compared to control negative. Interestingly, 500 mg/kg of MPAE showed a significant difference when compared to control negative for penile erection index. Positive increment can also be seen in the sperm count and sperm viability in sperm parameters. Additionally, after 4 weeks of treatment, MPAE treated rats showed an increment in testosterone level. 500 mg/kg of MPAE group showed a significant difference compared to negative control group. Overall, this study demonstrates the potential use of Melicope pteleifolia for aphrodisiac potential to help suppress infertility problem.